Antifungal, Plant Growth-Promoting, and Genomic Properties of an Endophytic Actinobacterium Streptomyces sp. NEAU-S7GS2 - Liu, Dongli; Yan, Rui; Fu, Yansong; Wang, Xiangjing; Zhang, Ji; Xiang, Wensheng (Frontiers in Microbiology, 2019)
Diseases caused by Sclerotinia sclerotiorum have caused severe losses of many economically important crops worldwide. Due to the long term persistence of sclerotia in the soil and the production of air-borne ascospores, the synthetic fungicides play limited role to control the diseases. The application of antagonistic microorganisms can effectively reduce the number of sclerotia and eventually eradicate S. sclerotiorum from soil, therefore considerable interest has been focused on biological control. Streptomyces sp. NEAU-S7GS2 was isolated from the root of Glycine max and its rhizosphere soil. It showed significantly inhibitory activity against the mycelial growth of S. sclerotiorum with an inhitory ratio of 99.1% and completely inhibited the sclerotia germination. In the pot experiment, compared to the control, the application of NEAU-S7GS2 not only demonstrated excellent potential to control sclerotinia stem rot of soybean with 77% and 38% decrease in disease incidence and disease index, respectively, but could promote the growth of soybean. The light microscope and scanning electron microscopy showed that co-culture of NEAU-S7GS2 with S. sclerotiorum on potato dextrose agar could lead to contorted and fragmented mycelia of S. sclerotiorum, which was associated with the secretion of hydrolytic glucanse and cellulase and the production of active secondary metabolites by NEAU-S7GS2. The plant growth promoting activity of NEAU-S7GS2 was related to the solubilization of inorganic phosphate, and production of 1-aminocyclopropane-1-carboxylate (ACC) deaminase and indole acetic acid (IAA). To further explore the plant growth promoting and antifungal mechanisms, the complete genome of strain NEAU-S7GS2 was sequenced. Several genes associated with ammonia assimilation, phosphate solubilization and IAA synthesis together with genes encoding ACC deaminase, glucanase and α-amylase were identified. AntiSMASH analysis led to identification of four gene clusters responsible for the biosynthesis of siderophores including desferrioxamine B and enterobactin. Moreover, the biosynthetic gene clusters of lydicamycins, phenazines and a glycosylated polyol macrolide showing 88% gene similarity to PM100117/PM100118 were identified. These results suggested that strain NEAU-S7GS2 may be a potential biocontrol agent and biofertilizer used in agriculture.